(untitled) (Journal of the Society for Musicology in Ireland, 2016)
A review of Lauri Suurpää, Death in Winterreise. Musico-poetic Associations in Schubert’s Song Cycle (Bloomington: Indiana University Press, 2014). ISBN 978-0-253-01100-8.